Nightclubbing: Montréal’s Lime Light - Pemberton, Rollie (Red Bull Music Academy, 2016)
The Lime Light and its innovative DJ Robert Ouimet made Montreal a disco city during the ’70s. This is the club's story.

Montréal Rave: An Oral History - Borzeix, Olivier (Red Bull Music Academy, 2016)
Tiga, Christian Pronovost, Jeff Waye and more remember the golden era of raves in Montréal.

C'est vital. Portraits dynamiques de la production culturelle autochtone en milieu urbain au Québec - Abitbol, Jonathan; Audet, Véronique; Gaudet, Janice Cindy; Guimont Marceau, Stéphane; Maltais-Landry, Aude; Lumsden, Mélanie; Parent, Marie-Josée (DestiNATIONS : Carrefour International des Arts et Cultures des Peuples autochtones, 2016)
DestiNATIONS est un projet culturel fédérateur autochtone d’envergure internationale basé à Montréal. Il émerge du RÉSEAU pour la stratégie urbaine de la communauté autochtone à Montréal, une association qui représente plus de 950 membres organisationnels et individuels de la communauté autochtone de Montréal. Le RÉSEAU a fait de ce projet d’ambassade culturelle autochtone une priorité transversale. DestiNATIONS s’est incorporé en mars 2014 et a tenu son assemblée générale de fondation le 21 mai 2015. DestiNATIONS a pour mandat de diffuser, promouvoir, produire, rechercher, soutenir et commanditer des produits artistiques, éducatifs et culturels multidisciplinaires (films, jeux vidéo, réalités virtu elles, danses, sculptures, musiques, artisanats, etc.) des Peuples autochtones, d’éduquer les publics sur les cultures autochtones traditionnelles et contemporaines et d’accueillir des rassemblements artistiques, politiques et culturels. DestiNATIONS est un lieu de rassemblement pour les Autochtones. DestiNATIONS est aussi un pôle de diffusion et de production de calibre international dédié à la découverte des cultures autochtones pour le plus grand plaisir des visiteurs et touristes internation aux. En 2015, DestiNATIONS s’est associé à Tourisme Autochtone Québec pour poursuivre la réalisation du projet d’infrastructure culturel et touristique de 6000 mètres carrés, basé à Montréal, appelé Legs des Premières Nations et des Inuits.

Where Is She? Finding the Women in Electronic Music Culture - Abtan, Freida (Contemporary Music Review, 2016)
The author discusses the visibility and participation of women in electronic music culture. She argues that most electronic music social networks privilege male inclusion and success, and that skill-sharing is an important strategy to encourage women in the field. To seed this discussion, the author examines her own history with reflections on the gender dynamics within electronic music communities outside the academy, and the role that social and technical currencies play within them. She also discusses Ladies club, a music distribution project that led to several solo female electronic musicians taking the stage and organising events in Montreal during 2007.
Keywords: Culture; Electronic Music; Feminism; Gender; Skills-Sharing

The Transmemoric Process: The Journey of Italian-Québécois Artists - Aloisio, Anita (Université Concordia, 2016)
The author focuses on the multilayered social identities internalized by seven second-generation Italian-Quebec artists and how it is manifested in their artwork. She examines how Quebec's political landscape, especially the impact of Quebec's linguistic, nationalist and cultural debates, and the subjects' parents' experience of immigration, impinged on the artistic process and production. The author demonstrates how these artists connect their Italian ethnicity to a creative practice to achieve a sense of balance between family traditions, personal identity, and belonging. The seven artists are: Vittorio Rossi (Playwright, Actor); Agata De Santis (Documentary Filmmaker, Producer, Blogger); Sandra Coppola (Filmmaker, Scriptwriter); Luisa Pepe (Singer, Songwriter); Franco Taddeo (Comedian); Michaela Di Cesare (Playwright, Actor); and Marco Calliari (Author, Composer, Musician).

La réception du hip-hop chez des rappeurs afro-québécois dans la ville de Québec : appropriation intersectionnelle de problématiques multidimensionnelles - Atséna Abogo, Marie Thérèse (Université Laval, 2016)

Creative layers and continuities: A case study of Nicole Lizée and the Kronos Quartet - Bayley, Amanda; Lizée, Nicole (Musicae Scientiae, 2016)
This study examines the creative layers and continuities evident within the composition and rehearsal processes of Nicole Lizée’s Golden Age of the Radiophonic Workshop (Fibre-Optic Flowers), written for the Kronos Quartet in 2012. Lizée’s compositional approach to the historic and the new, and the mechanical and the human, are interpreted through Simon Emmerson’s three themes of combination, transformation, and control, and his three “impulses within composition” that combine live and acousmatic soundworlds – integration, antithesis, and co-existence. These concepts also help to articulate the way the players engage with the physical, psychological, and expressive demands of the piece. Discussions arising from the Kronos Quartet rehearsing the piece with the composer reveal how extensions are made to the performers’ mind and body experiences when they are required both to initiate and integrate sounds emanating from unfamiliar, analogue machines into their acoustic, yet amplified soundworld. Creative layers and continuities are seen to evolve from compositional experimentation and from composer–performer and co-performer dialogues in rehearsal in the BBC Maida Vale studio prior to the world premiere at a BBC Prom concert on 24 July 2012.
Publisher: SAGE Publications Ltd
Keywords: Delia Derbyshire; Kronos Quartet; Radiophonic Workshop; composition; creativity; electronic sounds; interaction; notation; rehearsal; string quartet

Le Club musical de Québec : 125 ans - Bernier, Emmanuel (Cap-aux-Diamants, 2016)

Robert Ouimet and Pierre Gagnon - Burns, Todd L. (Redd Bull Music Academy, 2016)
Explore the Red Bull Music Academy archive, tracing the global music institution’s more than 20-year history

Éva Gauthier. La voix de l’audace - Cazelais, Normand (Fides, 2016)

De l’homosexualité à l’opéra - Champagne, Éric (L’Opéra : revue québécoise d’art lyrique, 2016)
Créée à l’Opéra de Montréal, l’œuvre de Kevin March, Les Feluettes, sur un livret de Michel Marc Bouchard, aborde de front une histoire d’amour entre deux hommes. Si les sujets homosexuels nous semblent communs dans la littérature, le théâtre et le cinéma, il faut se rendre à l’évidence qu’ils sont, du moins jusqu’à tout récemment, peu présents dans le monde de la musique, tous styles confondus. On entend beaucoup dire ces jours-ci que le genre de l’opéra, au public réputé conservateur, ne s’intéresse à cette thématique que depuis peu. Il s’agit en fait d’une demi-vérité, car s’il est vrai que l’homosexualité comme sujet principal n’est présent explicitement que dans des créations récentes, il se retrouve occasionnellement, caché ou crypté, dans diverses œuvres qui traversent son histoire vieille de plus de 400 ans.

The Songs of Violet Archer: Tracing the Evolution of One of Canada's Most Prominent Composers - Dauphinais, Paul (Université de Boston, 2016)
In this study, four sets of songs composed by Violet Archer are examined, all of which were written at different points in her career. Archer studied with Paul Hindemith in 1948 – 49, and his teachings had a tremendous impact on the young composer. The first set of songs to be analyzed, Moon Songs, was written before her time with Hindemith, and will provide a baseline from which her later, post-Hindemith, works can be compared. Following her studies with Hindemith, Archer wrote three songs, “Cradle Song,” “April Weather,” and “First Snow,” all of which show evidence of Hindemith’s influence. Her later, more mature works, Northern Landscape and Caleidoscopio Quatro, demonstrate a refined compositional technique; one in which Archer has created her own style, while maintaining aspects of the approach taught by Hindemith at Yale. This study will elaborate on the aspects of Archer’s music that evolved throughout her compositional career.
ISBN: 9781369365658
Keywords: Archer; Communication and the arts; Hindemith; Music analysis; Paul; Social sciences; Violet

Paroles inuites : création et transmission dans la chanson du Nunavik - Duvicq, Nelly (Recherches amérindiennes au Québec, 2016)
Among the forms of oral history, the song, within the Inuit culture, was general practice and quite versatile. Inheriting this tradition, the contemporary Inuit song has risen in popularity starting in the 1970’s and has not diminished since. Within the literary field, the lyrics to the Inuit songs demonstrate a remarkable vitality in which the author-composers explore various aesthetics, navigate languages and transmit a part of their culture. Taking into consideration the historical context, this article aims to reflect on the formal evolution of the modern Inuit song and examine the relations that are maintained through more traditional portrayals. Finally, the ultra-contemporary body of musical works in Nunavik is notable for being particularly trilingual yet reveals an upsurge of texts in Inuktitut. What significance will this have on the overall discourse?
Publisher: Recherches amérindiennes au Québec
Keywords: Inuit literature; Inuit songs; Inuktitut; Nunavik; canción inuit; chanson inuite; inuktitut; literatura inuit; littérature inuite; oralidad; orality; oralité

Claude Vivier at the End - Goldman, Jonathan (Contemporary Music and Spirituality, 2016)

Entendu dans Cette ville étrange : « Fuck toute ! » – une génération de compositeur·e·s décomplexe sa marge - Henry, Symon (Circuit, 2016)
Publisher: Les Presses de l’Université de Montréal
Keywords: Pas sur genres ou/et sexualités

Rap, genre, langage et québéquicité : enjeux et tensions sociolinguistiques de l’accès aux espaces médiatiques à Montréal - Lesacher, Claire (Cahiers internationaux de sociolinguistique, 2016)
Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 0 Publisher: L'Harmattan

DJ Mini and Montreal’s Vulgar Dance Music - Madden, David (Dancecult, 2016)
This article advances claims about Montreal’s electronic dance music scene through mapping the career of one of the key actors who shaped the electroclash scene from the early 2000s onwards—music producer/DJ Mini (née Evelyne Drouin). By way of detailing the career of DJ Mini, this text attempts to add to the queer musical narratives currently emerging from music scene analyses. Counter to the experiences of many women DJs and musicians participating in heterosexual and male-dominated music scenes, Drouin received extensive mentoring and support from various informal queer social networks spread throughout the circuits of the city. Not only did she gain access to a local production network of equipment and skill sharing, Drouin was also given access to spaces where she was able to develop production skills on her own time and at her own pace. DJ Mini’s story offers a telling case for the ways in which the politics of access—institutional, social, technological—remain central to the vitality and inclusivity of local music scenes.

Analyses of Organ Etudes Opp. 38, 66 and 72 by Rachel Laurin - Mateva, Silviya (Université d'Oklahoma, 2016)

Listening to "Mes lames de tannage": Notes toward a Translation - Moyes, Lianne (Canadian Literature, 2016)

On the Internet by Means of Popular Music: The Cases of Grimes and Childish Gambino - Ohlendorf, Kristopher R. K. (Université Western Ontario, 2016)
What is the internet? It began as a military research experiment, but the internet has since become a sweeping cultural phenomenon. One of the most prevalent areas of the internet’s cultural dominance is in popular music, and this thesis addresses how the internet is being understood and discussed by popular music artists. I study the works of Grimes and Childish Gambino, two popular music artists who grew up alongside the internet’s rise to cultural dominance and explicitly address this experience as an integral component of their lives and works. I look specifically at discourse surrounding Grimes’ “post-internet” music and Childish Gambino’s expansive conceptual work Because the Internet (2013). This research concludes by addressing how popular music artists like Grimes and Childish Gambino are helping produce the ways in which we understand and discuss the cultural phenomenon of the internet, and how they provide a foundation for future artists and research to build upon.

« La terre qui nous a vus grandir ». Le sujet et le monde chez Mara Tremblay, Ariane Moffatt et Salomé Leclerc - Pirie, Nathan (Université de Waterloo, 2016)
Cette étude inclut les œuvres de Mara Tremblay, Ariane Moffat et Salomé Leclerc et vise un objectif double : d’une part, il s’agit d’analyser des textes lyriques qui ont une indéniable qualité poétique et d’autre part, de réaliser une étude intermédiale alliant texte, musique et clip-vidéo afin de voir comment le sens d’un de ces éléments est infléchi, modifié ou complété par celui des autres éléments. L’hypothèse de recherche est qu’aujourd’hui, les auteurs-compositeurs-interprètes conçoivent leur art à travers trois langages esthétiques (le texte, la musique et la vidéo), faisant de la musique une expérience plurisensorielle et intermédiale. Pour faire émerger le message de ces artistes, on mobilisera les théories du care et l’écoféminisme afin d’analyser le discours portant sur le sujet et le monde. On vise à dégager les grands thèmes de ces œuvres à travers une synthèse de ces trois approches critiques. L’analyse du corpus vise à déterminer la qualité poétique des textes et la vision du monde que ces trois artistes diffusent.

True Loves, Dark Nights: Queer Performativity and Grieving Through Music in the Work of Rufus Wainwright - Salerno, Stephanie (Université d'État de Bowling Green, 2016)

Vers une reconstitution de la vie culturelle des femmes à Montréal dans les années 1940 - Savoie, Chantal (Voix et Images, 2016)

Écritures chorégraphiques et sonores imbriquées : récits de collaborations avec Danièle Desnoyers - Tobin, Nancy (L’Annuaire théâtral : revue québécoise d’études théâtrales, 2016)
Ce texte revient sur le processus de création de trois spectacles chorégraphiques auxquels j’ai participé comme conceptrice sonore : Concerto grosso pour corps et surface métallique (1999), Duos pour corps et instruments (2003) et Là où je vis (2007). Ces parcours de recherche-création, traversés avec la chorégraphe Danièle Desnoyers (compagnie Le Carré des Lombes), permettent d’observer comment l’écriture sonore se développe in situ avec l’écriture chorégraphique. Les deux se forment ensemble en s’influençant l’une l’autre. Les trois spectacles choisis témoignent de différents modes de création de la matière sonore : amplification des danseurs, diffusion avec des haut-parleurs inusités, invention d’instruments et citation de musiques transformées. Les récits de collaborations qui suivent révèlent les manières dont la matière sonore a émergé de l’écriture chorégraphique et vice versa.

Changing openness and tolerance towards LGBTQ singer-songwriters - Williams, Katherine (The Cambridge Companion to the Singer-Songwriter, 2016)
Most often associated with modern artists such as Bob Dylan, Elton John, Don McLean, Neil Diamond, and Carole King, the singer-songwriter tradition in fact has a long and complex history dating back to the medieval troubadour and earlier. This Companion explains the historical contexts, musical analyses, and theoretical frameworks of the singer-songwriter tradition. Divided into five parts, the book explores the tradition in the context of issues including authenticity, gender, queer studies, musical analysis, and performance. The contributors reveal how the tradition has been expressed around the world and throughout its history to the present day. Essential reading for enthusiasts, practitioners, students, and scholars, this book features case studies of a wide range of both well and lesser-known singer-songwriters, from Thomas d'Urfey through to Carole King and Kanye West.

Rufus Wainwright - Williams, Katherine (Equinox Publishing, 2016)
Canadian-American singer-songwriter Rufus Wainwright is famous around the world for his multi-faceted musical style, shown through both his recorded output and his engaging live performances. Katherine Williams combines aspects of his life story with scholarly readings drawn from several methodologies.